ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI GOING CONCERN PADA PERUSAHAAN MANUFAKTUR PERIODE 2018-2020 - Wilsen Tanadi; Jamaludin Iskak (Jurnal Paradigma Akuntansi, 2023)
This research was conducted to examine the effect of liquidity, profitability, growth,firm size, and previous year's audit opinion on the formation of going concern opinionson manufacturing sector that listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. The sample was selected by purposive sampling method and the valid data were 32 companies. The data processing technique uses logistic regression analysis supported by SPSS software (Statistical Product and Service Solution) 25 program for Windows and Microsoft Excel 2019. The results show that liquidity, profitability, growth and firm size have no effect on the formation of a going concern opinion. While, the previous years audit opinion had a positive effect on the formation of a goingconcern opinion.